The use of information and communication technology in pedagogical documentation: an investigation of early childhood education in China. Issue 2 (4th March 2022) - Yang, Tian; Chan, Angel; Gunn, Cathy
ABSTRACT: Pedagogical documentation has been regarded as an important practice in early childhood education (ECE) settings because it provides an opportunity to observe children's learning and help teachers plan for learning experiences. This article focuses on teachers' use of information and communication technology (ICT) in pedagogical documentation in an under-researched context. A qualitative study was conducted in three kindergartens in Nanjing, China, over five months. The Technological Pedagogical and Content Knowledge (TPACK) model was adopted to understand participants' decision-making about pedagogical documentation. Findings indicate that ICT-supported pedagogical documentation aimed to help children learn from peers' experiences and reflect on their own learning. Participants considered pedagogical documentation as a tool for initiating discussion with children, though few used it to plan for future learning experiences. A gap between practice and policy in relation to pedagogical documentation was found in the study, and implications for both areas are discussed.